PENINGKATAN PENGETAHUAN TERKAIT DAMPAK FISIOLOGIS STUNTING YANG TERJADI PADA FASE REMAJA MELALUI SOSIALISASI SECARA DARING (STIKes Mitra Keluarga, 2024)
Stunting is a condition of chronic malnutrition that can have short-term and long-term impacts on a child's growth and development. Children who have a history of stunting can experience physiological disorders, one of which is during adolescence. However, not all people know the physiological impact of stunting that is felt during adolescence. Therefore, an online outreach activity was held during the Covid 19 pandemic. This activity aims to increase public knowledge regarding the physiological impact of stunting that occurs in the adolescent phase. The activity was attended by students, health workers and the general public. A total of 175 participants completed the pre and post test activities. It was recorded that there was a significant increase in knowledge as measured using the Wilcoxon Signed Rank statistical test (p<0.05). At the end of the activity, it can be concluded that there is an increase in knowledge regarding the physiological impact of stunting that occurs in the adolescent phase from activities carried out online.